Through superheroes, America spreading religious propaganda - Meyfian, Raka Elda (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
This article explores the role of propaganda in shaping religious narratives through the lens of superhero films. Propaganda's ability to frame narratives and influence how individuals interpret historical events is crucial in determining whether an event or history is perceived as good or bad. By selectively highlighting aspects that serve specific agendas, propaganda integrates its messages into our daily lives almost unnoticed. Various mediums, particularly film, serve as effective tools for disseminating propaganda, with superhero films like